THE STATE OF THE COSMOLOGICAL MODEL: OBSERVATIONS AND THEORY - Lukash, V. N. (Одеські астрономічні публікації, 2017)
The main points and trends of observational and theoretical cosmology that influence and form the understanding of the Universe are reviewed.